2010
DOI: 10.1161/hypertensionaha.109.147850
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Destiffening With Weight Loss in Overweight and Obese Middle-Aged and Older Adults

Abstract: Abstract-We tested the hypothesis that weight loss via a hypocaloric diet would reduce arterial stiffness in overweight and obese middle-aged and older adults. Thirty-six individuals were randomly assigned to a weight loss (nϭ25; age: 61.2Ϯ0.8 years; body mass index: 30.0Ϯ0.6 kg/m 2 ) or a control (nϭ11; age: 66.1Ϯ1.9 years; body mass index: 31.8Ϯ1.4 kg/m 2 ) group. Arterial stiffness was measured via carotid artery ultrasonography combined with applanation tonometry and carotid-femoral pulse wave velocity via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
122
3
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(139 citation statements)
references
References 24 publications
12
122
3
2
Order By: Relevance
“…50 Two interventional studies have recorded a small fall in PWV after weight loss in overweight or obese middle-aged adults but whether the effect is similar in younger adults remains unknown. 9,51 The relationship between excess cardiovascular risk and the degree of obesity is nonlinear, and our findings indicate that the cardiovascular response to dietary interventions might be expected to vary according to age group and the proportion of body fat at baseline. [52][53][54] Further research is needed to determine in which obesity phenotypes and age groups weight loss interventions are most effective in leading to improved cardiovascular outcomes.…”
Section: Discussionmentioning
confidence: 93%
“…50 Two interventional studies have recorded a small fall in PWV after weight loss in overweight or obese middle-aged adults but whether the effect is similar in younger adults remains unknown. 9,51 The relationship between excess cardiovascular risk and the degree of obesity is nonlinear, and our findings indicate that the cardiovascular response to dietary interventions might be expected to vary according to age group and the proportion of body fat at baseline. [52][53][54] Further research is needed to determine in which obesity phenotypes and age groups weight loss interventions are most effective in leading to improved cardiovascular outcomes.…”
Section: Discussionmentioning
confidence: 93%
“…Increased arterial stiffness in this mouse model is related to sympathetic nervous system activation, reduced nitric oxide bioactivity, and inflammation. Voluntary weight loss with a low‐calorie diet for 12 weeks is associated with a decrease in arterial stiffness in overweight/obese, middle‐aged, and elderly subjects 121. The decrease in arterial stiffness correlates with a reduction in total body weight and abdominal obesity 121.…”
Section: Obesity Phenotypementioning
confidence: 99%
“…Voluntary weight loss with a low‐calorie diet for 12 weeks is associated with a decrease in arterial stiffness in overweight/obese, middle‐aged, and elderly subjects 121. The decrease in arterial stiffness correlates with a reduction in total body weight and abdominal obesity 121. Aerobic exercise training and a low‐calorie diet for 7 weeks reduces arterial stiffness to a greater extent than diet alone in morbidly obese subjects 122.…”
Section: Obesity Phenotypementioning
confidence: 99%
“…The present study adds to a number of investigations, which have consistently shown a reduction in cfPWV over the short term, following different lifestyle interventions, including not only physical exercise [11][12][13][14][15][16] but also weight loss, smoking cessation and salt intake restriction [17][18][19][20][21][22][23][24][25] (Table 1).…”
mentioning
confidence: 58%